An Improved Multiobjective Model-Predictive Control Method for Active Neutral-Point-Clamped Five-Level Converter - Qiguang Ren; Chang Liu; Xiangyang Xing; Rui Zhang; Chenghui Zhang (IEEE Open Journal of the Industrial Electronics Society)
The active neutral-point-clamped five-level converter has drawn much attention in industrial applications. However, common-mode voltage (CMV) suppression, accurate track current, fixed switching frequencies, neutral-point (NP) voltage balance, and flying capacitor (FC) voltage are compulsory in this configuration. Thus, an improved multiobjective model-predictive control (IMMPC) without weighting factors is proposed in this article. First, to suppress CMV, only 61 low-CMV vectors out of 125 vectors were selected. Second, to ensure current tracking performance and reduce computational burden, based on the gh oblique coordinate, three voltage vectors were calculated online in each control period, which can avoid lookup tables. Third, the optimal switching sequence and duty cycles were presented considering the lowest switching numbers and constant switching frequency. A high-quality current was thus obtained, and the NP voltage and the FC voltage were balanced by selecting switching combinations. The IMMPC can be applied to other multilevel converters for current tracking and CMV suppression with a simple adjustment on parameters. Finally, the feasibility and the effectiveness of the proposed method were verified through simulations and experiments.